Allogeneic Hematopoietic Stem Cell Transplantation for Mixed or Overlap Myelodysplastic/Myeloproliferative Disorders - Symeonidis, Argiris; Chondropoulos, Spiros; Verigou, Evgenia; Lazaris, Vasileios; Kourakli, Alexandra; Tsirigotis, Panagiotis (Frontiers in Oncology, 2022)
Chronic myelomonocytic leukemia (CMML) and the remaining, less frequent hybrid, mixed or overlap myelodysplastic syndromes/myeloproliferative neoplasms (MDS/MPN) are difficult to treat neoplastic hematological disorders, exhibiting substantial clinical and prognostic heterogeneity, for which clear therapeutic guidelines or effective treatment options are still missing. CMML has an overall survival ranging from few months to several years. Although patients with proliferative or dysplastic features may benefit from hydroxyurea and hypomethylating agent treatment, respectively, none of these treatments can establish long term remission and prevent the inevitable transformation to acute leukemia. Novel, targeted treatment approaches are emerging, but are still under investigation. Therefore, currently, allogeneic stem cell transplantation (Allo-SCT) remains the only treatment modality with a curative potential, but its widespread application is limited, due to significant morbidity and mortality associated with the procedure, especially in the elderly, and in patients with comorbidities. Recognition of patient’s eligibility for Allo-SCT is crucial and the procedure should be addressed to patients with a good performance status, without severe comorbidities and mainly to those in intermediate to high-risk category, with a suitable stem cell donor available. The issues of best timing for performing transplantation, patient and donor eligibility, the type of conditioning regimen and the outcomes after various Allo-SCT procedures are the topic of this review.